Approaching a decade since HPV vaccine licensure: Racial and gender disparities in knowledge and awareness of HPV and HPV vaccine - Eric Adjei Boakye; Betelihem B. Tobo; Rebecca P. Rojek; Kahee A. Mohammed; Christian J. Geneus; Nosayaba Osazuwa-Peters (Taylor & Francis Group, 2017)
Purpose: Gaps remain in the public's knowledge of the human papillomavirus (HPV). We assessed racial/ethnic and gender disparities in knowledge and awareness of HPV and the HPV vaccine among US adults. Methods: Data from the Health Information National Trends Survey 4 Cycle 3 (September - December 2013) and Cycle 4 (August - November 2014) were analyzed for 6,862 respondents aged 18 years and older. Weighted multivariable logistic regression models were used to estimate racial/ethnic and gender disparities in HPV knowledge and HPV vaccination awareness. Results: Sixty-six percent of respondents had heard of HPV and the HPV vaccine (57% of men vs. 75% of women). In multivariable analyses, compared with men, women were 225% (95% CI: 2.60 - 4.07) more likely to have heard of HPV, and 281% (95% CI: 3.06 - 4.74) more likely to have heard of the HPV vaccine. Non-Hispanic Blacks were 33% (95% CI: 0.47 - 0.96) and 44% (95% CI: 0.39 - 0.81) less likely than non-Hispanic Whites to have heard of HPV and the HPV vaccine, respectively. Hispanics were 27% (95% CI: 0.52 - 1.02) and 53% (95% CI: 0.34 - 0.64) less likely than non-Hispanic Whites to have heard of HPV and the HPV vaccine, respectively. Conclusions: There was evidence of disparities in HPV and HPV vaccine awareness among men compared with women and non-Hispanic Blacks and Hispanics compared with non-Hispanic Whites. To foster improvements in HPV vaccine uptake and reduce disparities in HPV associated cancers, future interventions must target men and minority populations, for whom knowledge gaps exist.